Cocaine, Death Squads, and the War on Terror : U.S. Imperialism and Class Struggle in Colombia - Villar, Oliver; Cottle, Drew (Book collections on Project MUSE., 2011)
Since the late 1990s, the United States has funneled billions of dollars in aid to Colombia, ostensibly to combat the illicit drug trade and State Department-designated terrorist groups. The result has been a spiral of violence that continues to take lives and destabilize Colombian society. This book asks an obvious question: are the official reasons given for the wars on drugs and terror in Colombia plausible, or are there other, deeper factors at work? Scholars Villar and Cottle suggest that the answers lie in a close examination of the cocaine trade, particularly its class dimensions. Th.